2017
DOI: 10.1108/ec-03-2016-0090
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation of transient MHD free convective flow of a nanofluid over a moving semi-infinite vertical cylinder

Abstract: Purpose-The purpose of this paper is to study numerically the influence of a magnetic field on the transient free convective boundary layer flow of a nanofluid over a moving semi-infinite vertical cylinder with heat transfer Design/methodology/approach-The problem is governed by the coupled non-linear partial differential equations with appropriate boundary conditions. The fluid is a water-based nanofluid containing nanoparticles of copper. The Brinkman model for dynamic viscosity and Maxwell-Garnett model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 26 publications
0
18
0
Order By: Relevance
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 95%
“…They studied the effects of the Rayleigh number, fin length, oscillating amplitude, oscillating period, thermal conductivity ratio (fin to fluid) and the non-dimensional Young's modulus. Other research studies can be found in literature (Ghalambaz and Noghrehabadi, 2014; Ghalambaz et al , 2014a, 2014b, 2019; Noghrehabadi et al , 2012a, 2012b, 2012c, 2013a, 2013b, 2014; Mansour et al , 2016; Ahmed et al , 2013; EL-Kabeir et al , 2007; Rashad, 2008; Rashad et al , 2011, 2017a, 2017b; Gorla et al , 2011; Sivasankaran et al , 2016; Liu et al , 2019; Aly and Pop, 2019; Nasrin et al , 2019; Sreedevi et al , 2019; Hayat et al , 2015; Mohammed et al , 2012; Makinde (2013); Şenay et al , 2019; Prakash and Agrawal, 2016; Rajesh et al , 2017; Khamis et al , 2015; Alsabery et al , 2019; Vemula et al , 2016; Fornalik-Wajs et al , 2019; Sun and Pop, 2014; Malvandi et al , 2017; Thumma et al , 2017; Rawat et al , 2019; Venkateswarlu et al , 2019a, 2019b). In these research works, different nanofluid parameters and various numerical and experimental models were addressed.…”
Section: Introductionmentioning
confidence: 95%
“…The different surface geometry and boundary condition will be among the factors that affect the heat transfer parameter. [44] CWT Vertical Cylinder FDM Crank Nicolson Thumma et al, [39] CWT Rotating Vertical porous plate Finite Element Method Thumma et al, [40] CWT Moving Inclined porous Plate Finite Element Method Kumar & Kumar [42] CWT Stretching Sheet Runge Kutta 4 th Kumar & Kumar [58] CWT Vertical Plate Laplace Transform Sravanthi [41] CHF Stretching Vertical Cylinder Homotopy Analysis Method…”
Section: Nanofluid Models 361 Tiwari and Dasmentioning
confidence: 99%
“…Later, Rajesh et al 6 explored the nanoliquid motion over an impulsively started vertical surface with changeable temperature. Other pertinent studies subject to nanofluid have been examined by Rajesh et al 7‐10 Seth et al 11 investigated entropy generation in a hydromagnetic nanofluid flow over a nonlinear stretching sheet with Navier's velocity slip and convective heat transfer. Additional studies on nanofluid convection flows have been archived by Das et al 12 and in the review articles of Wang and Mujumdar, 13‐15 Kakac and Pramuanjaroenkij, 16 Kasaeian et al, 17 and Lin and Yang 18 …”
Section: Introductionmentioning
confidence: 99%